Comportamento, competência social e qualidade de vida na Doença de Huntington - Silva, Caroline Stephanie Da; Lindau, Tâmara Andrade; Giacheti, Célia Maria (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
ABSTRACT:Purpose: investigating the behavior, the social competence and the quality of life of individuals who carry Huntington Disease.Methods: the sample was constituted for 30 participants, from 33 to 79 years old, divided in two groups: 15 participants in the experimental group, who were previously diagnosed with Huntington Disease and 15 participants in the comparative group, equally paired according to age and education. To assess this individuals were applied, on their caregivers, the Behavioral Inventory, constituted by the Adult Behavior Checklist and the Quality of Life Questionnaire WHOQOL - 100 were used to asses these individuals.Results: the individuals in the experimental group have presented statistically significant differences when compared to the control group, according to their caregivers' opinion, with high scores for internalizing factors (anxiety, depression, isolation, somatic complaints), total problems and other problems like: thinking, attention and hyperactivity problems, from the behavioral inventory. In the Quality of Life Questionnaire the experimental group has also presented statistically significant differences when compared to the control group, in all domains (physical, psychological, level of independence, social relationships, environment and religious aspects) and in most of the assessed aspects they presenting a low average of quality of life, while the control group has presented a high average.Conclusion: individuals with HD present behavioral, social competence and quality of life profile differentiated and with alterations, according to their caregivers, when it was related to the comparative group. Huntington's disease is limiting, progressive and also appears to be responsible for the set of behavioral change, social competence and quality of life reported by their caregivers.

RESUMO:Objetivo: investigar o comportamento, a competência social e a qualidade de vida de indivíduos com a Doença de Huntington (DH), segundo opinião de seus cuidadores.Métodos: constituíram a casuística 30 participantes, com faixa etária de 33 a 79 anos, subdivididos em dois grupos: 15 do grupo amostral (GA) diagnosticados previamente com Doença de Huntington e 15 participantes do grupo controle (GC), pareados quanto à faixa etária, gênero e classificação socioeconômica. Para avaliação destes sujeitos foram aplicados, em seus cuidadores, o Inventário Comportamental Adult Behavior Checklist e o Questionário de Qualidade de Vida WHOQOL-100.Resultados: na avaliação do comportamento e da competência social, os sujeitos do GA apresentaram diferença estatisticamente significante em relação ao GC, segundo opinião dos seus cuidadores, com escores elevados para fatores internalizantes (ansiedade, depressão, isolamento, queixas somáticas), totais de problemas e outros, como problemas do pensamento, atenção e hiperatividade. No questionário de qualidade de vida, para sujeitos com a DH também se evidenciou diferença estatisticamente significante em relação ao grupo controle, em todos os domínios (físico, psicológico, nível de independência, relações sociais, ambiente e aspectos religiosos) e na maioria dos subitens avaliados. O GA apresentou média baixa de qualidade de vida, enquanto o GC apresentou média alta.Conclusão: sujeitos com DH possuem um perfil comportamental, de competência social e qualidade de vida diferenciado e com mais alterações, em relação ao GC, segundo os cuidadores . A Doença de Huntington parece ser responsável pelo conjunto de alterações comportamentais, de competência social e de qualidade de vida, relatado pelos cuidadores.
Behavior, social competence and quality of life in Huntington's Disease
Keywords: Huntington Disease; Behavior; Social Behavior; Quality of Life; Doença de Huntington; Comportamento; Comportamento Social; Qualidade de Vida